Tree cover and carbone dioxide capture in urban parks : Case: Northern Lima - Arévalo Gómez, Walter Aparicio (2021)
The objective of this research was to determine the relationship between tree cover and carbone dioxide capture in urban parks in Northern Lima. For its development, a research with a quantitative approach and correlational type was designed. The methodology used consisted of field work and remote work. Through the field work, information was obtained about the coverage and tree structure of the parks and the remote work allowed to determine the volumes of CO2 captured by the parks. This process was carried out through the Software i- Tree Canopy. The research was carried out in northern Lima, specifically in the districts of Los Olivos, Comas, San Martín de Porres and Independencia. The correlation analysis was carried out using the Pearson coefficient. The results obtained, 0.994 Pearson correlation, show a particularly good positive relationship between tree cover and carbon capture of the parks in the study area, however the values obtained regarding the volume of carbone dioxide capture (0.34 CO2/m2-año) are very low compared to the results of research conducted in other cities.